Is international security completely attained nowadays? - Sergaliyeva Milana Aslanovna (Foundations and Trends in Research, 2024)
When a country’s security is not ensured, the government tends to amend legislation, arrest a criminal or reallocate resources to guarantee an efficient function of security agencies, depending on the circumstances. However, in case of global law violations, is the world capable of a complete attainment of international peace and security nowadays? Barely managing to analyze the web of interconnected events and properly assess the extent of global order enforcement, many unconsciously overstate the latter, but the truth is reversed. Accordingly, the Diplomacy Network states: “It is crucial to note that international security is not a static concept and it is constantly evolving, as new challenges and threats arise.”[1] Therefore, this paper identifies and diversely examines the effectiveness of international institutions’ efforts to attain global safety over the last century.